PENGARUH PERHATIAN ORANGTUA TERHADAP PRESTASI BELAJAR DI SMPN 3 SIMPENAN TAHUN 2019 - Nawawi Nawawi (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2021)
student achievement (2) to determine the effect of parent attention on student achievement. Quantitative approach. Correlation method by explaining the relationship of variable X with variable Y, in this case correlation by explaining the relationship and the effect of parent attention on student achievement. The results of the study (1) there is a significant functional relationship between the variables of parent attention to student learning achievement. F count of tuna matches 1,154 <f table 2.42 meaning that the relationship of parent attention to learning achievement is linear, or the regression of Y over X is linear. (2) The magnitude of the effect of variable X on variable Y = 11.8%, the relationship of parent attention to student achievement = 0.343, the remaining 88.92% was determined by other factors. Keywords: Parent attention, Student learning, achievement